2011
DOI: 10.1029/2011jd016287
|View full text |Cite
|
Sign up to set email alerts
|

El Niño-Southern Oscillation and snow level in the western United States

Abstract: The relationship between El Niño–Southern Oscillation and the elevation of snow level in the western United States is established. Snow level variability is quantified from records of (1) wet‐bulb zero heights at ten rawinsonde sites (1957–2010), (2) empirically estimated snow levels over ten adjacent watersheds from precipitation and snowfall observations (∼1924–2009), and (3) 850–700 hPa thicknesses (1948–2010). The statistical relationship between these variables and the Southern Oscillation Index is establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…More recently, a second study by Schulte et al (2018) found the EP-NP pattern to be a dominant pattern governing LIS water temperature variability. The EP-NP pattern was shown to be strongly correlated with LIS water tem-perature unlike the well-known North Atlantic Oscillation (NAO; Hurrell, 1995), Pacific North American (PNA; Wallace and Gutzler, 1981;Svoma, 2011), Arctic Oscillation (AO; Thompson and Wallace, 1998), and West Pacific (WP; Barston and Livezey, 1987;Linkin and Nigam, 2008) patterns. In fact, Schulte and Lee (2017) found that the EP-NP pattern is more strongly related to temperature variability across the northeast US than the AO, which is often associated with colder-than-normal conditions across the region (Wettstein and Mearns, 2002).…”
Section: Introductionmentioning
confidence: 92%
“…More recently, a second study by Schulte et al (2018) found the EP-NP pattern to be a dominant pattern governing LIS water temperature variability. The EP-NP pattern was shown to be strongly correlated with LIS water tem-perature unlike the well-known North Atlantic Oscillation (NAO; Hurrell, 1995), Pacific North American (PNA; Wallace and Gutzler, 1981;Svoma, 2011), Arctic Oscillation (AO; Thompson and Wallace, 1998), and West Pacific (WP; Barston and Livezey, 1987;Linkin and Nigam, 2008) patterns. In fact, Schulte and Lee (2017) found that the EP-NP pattern is more strongly related to temperature variability across the northeast US than the AO, which is often associated with colder-than-normal conditions across the region (Wettstein and Mearns, 2002).…”
Section: Introductionmentioning
confidence: 92%
“…The EP-NP pattern was shown to be strongly correlated with LIS water tem-J. A. Schulte and S. Lee: Long Island Sound temperature variability perature unlike the well-known North Atlantic Oscillation (NAO; Hurrell, 1995), Pacific North American (PNA; Wallace and Gutzler, 1981;Svoma, 2011), Arctic Oscillation (AO; Thompson and Wallace, 1998), and West Pacific (WP; Barston and Livezey, 1987;Linkin and Nigam, 2008) patterns. In fact, Schulte and Lee (2017) found that the EP-NP pattern is more strongly related to temperature variability across the northeast US than the AO, which is often associated with colder-than-normal conditions across the region (Wettstein and Mearns, 2002).…”
Section: Introductionmentioning
confidence: 94%
“…Mountain snow line elevations, and hence the partitioning between rainfall and snowfall, are known to be sensitive to modes of interannual climate variability (e.g., Svoma 2011; Abatzoglou 2011) and show long-term trends (e.g., Knowles et al 2006;Svoma 2009) that have been attributed in part to anthropogenic climate change (Pierce et al 2008). The elevation of the surface transition between snowfall and rainfall-the mountainside snow line-plays a central role in determining roadway navigability, river runoff, freshwater resources, and hazards from landslides, avalanches, and floods.…”
Section: Introductionmentioning
confidence: 99%